Preliminary evidence that Clostridium perfringens type A enterotoxin is present in a 160,000-Mr complex in mammalian membranes. - Wnek, A P (1989)
Clostridium perfringens type A 125I-enterotoxin (125I-CPE) was bound to rabbit intestinal brush border membranes (BBMs) or Vero cells and then solubilized with 3-[(3-cholamidopropyl)dimethyl-ammonio]-1-propanesulfonate (CHAPS). Solubilized radioactivity was analyzed by gel filtration chromatography on a Sepharose 4B column or by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) without sample boiling and autoradiography. Specifically bound 125I-CPE extracted from either BBMs or Vero cells was primarily associated with a complex of approximately 160,000 Mr. The CPE complex was partially purified by gel filtration or SDS-PAGE without sample boiling. SDS-PAGE analysis with sample boiling of the partially purified 125I-CPE complex from Vero cells or BBMs suggested that CPE complex contains both a 50,000-Mr protein and a 70,000-Mr protein in approximately equimolar amounts. This result is supported by affinity chromatography with CPE immobilized on Sepharose 4B, which showed the specific interaction of similar size proteins with CPE. The simplest explanation for these results is that CPE (Mr 35,000) interacts with 50,000-Mr and 70,000-Mr eucaryotic proteins to form a membrane-dependent complex of approximately 160,000 Mr. These results suggest that the receptor or target site(s) or both for CPE are similar in both BBMs and Vero cells. The significance of these findings in terms of CPE binding, insertion, and biologic action is discussed.